Characterizing Angling Trends among Blue Marlin Anglers Following the 2008 Circle Hook Regulation - Kelly, Marisa Ann (East Carolina University, 2022)
The blue marlin Makaira nigricans (Lacepède, 1802) is a highly migratory, large pelagic predator that is subject to overfishing as bycatch in longline fisheries and as game fish in recreational tournaments, such as the Governor’s Cup tournament hosted along the coast of North Carolina. Catch-and-release methods and the use of circle hooks, which are designed to evade soft tissue and hook safely in the jaw, have been implemented in order to protect blue marlins from such effects. Circle hook regulations dictating whether artificial or natural baits can be paired with circle or J-style (straight) hooks were first applied to commercial fisheries, but were then expanded to recreational fisheries in 2008, given their increasing contribution to yearly blue marlin biomass. This study used data from the release forms collected from nine Governor’s Cup tournaments from 2007 to 2020 to evaluate changes in angling methods prior to and after the enactment of the 2008 recreational circle hook regulation. Trends in hook use and classification analyses predicting hook and bait combinations show general compliance to this regulation among all participating anglers. However, while J-hooks remained the preferred hook type among Big Rock anglers after 2007, other tournaments showed no preference for either hook type in years following the regulation.
Keywords: blue marlin, circle hooks, regulation